Potensi Cuka Apel (Apple Ciner Vinegar) dalam Menurunkan Kadar Kolesterol Total - Nazarudin, Muhammad; Torezellia, Cast; Sidiq, Abdurrahman; Ayanti, Bio Putri (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT World Health Organization in 2018, showed the prevalence of hypercholesterolemia in the world is around 45%, in Southeast Asia around 30% and 35% in Indonesia. Hypercholesterolemia is also a current problem due to the increasing variety of foods rich in fat. Many alternative choices have been used by the community. One of them is using Apple Cider Vinegar. Apple Cider Vinegar is believed to lower cholesterol levels. The purpose of this study was to determine the potential of apple cider vinegar in lowering total cholesterol levels by giving apple cider vinegar (Apple Cedar Vinegar) to male Rattus norvegicus rats of the Wistar strain. The research used was an experimental study using a post-test only control group design in 3 test groups. This research was conducted at the Clinical Pathology Laboratory, Microbiology Laboratory, Natural Materials Laboratory of Borneo Lestari University. The research objects were divided into a control group using Simvastatin solution, a negative control group, and a treatment group with apple cider vinegar solution. Based on the results of the ANOVA test, there was no significant difference between the 3 treatment groups. However, it shows the results of the closeness of the similarity of properties between simvastatin and apple cider vinegar in lowering cholesterol levels between the positive control group and apple cider vinegar, there is a similarity. Keywords: Contamination, Staphylococcus Aureus Bacteria, Soto Banjar.  ABSTRAK Data World Health Organitation (WHO) pada tahun 2018, menunjukkan prevalensi hiperkolesterolemia di dunia sekitar 45%, di Asia Tenggara sekitar 30% dan di Indonesia 35%. Hiperkolesterolemia juga merupakan masalah masa kini karena variasi makanan kaya lemak yang menigkat. Banyak pilihan alternatif yang telah digunakan masyarakat. Salah satunya menggunakan Cuka Apel. Cuka Apel dipercaya dapat menurunkan kadar kolesterol.  Tujuan dari penelitian ini adalah untuk mengetahui potensi cuka  apel dalam menurunkan kadar kolesterol total dengan memberikan cuka apel (Apple Cedar Vinegar) pada tikus jenis Rattus norvegicus jantan galur wistar. Penelitian yang digunakan adalah penelitian eksperimen menggunakan post tes only control grup design pada 3 kelompok uji. Penelitian ini di lakukan di Laboratorium Patologi klinik, Laboratorium Mikrobiologi, Laboratorium Bahan Alam Universitas Borneo Lestari. Objek penelitian dibagi kelompok kontrol menggunakan larutan Simvastatin, kelompok kontrol negatif, dan kelompok perlakuan dengan pemberian larutan cuka apel. Berdasarkan hasil uji ANOVA menujukkan tidak ada perbedaan signifikan antara 3 kelompok perlakuan. Namun, menunjukkan hasil kedekatan kemiripan sifat antara simvastatin dan cuka apel dalam menurunkan kadar kolesterol antara kelompok kontrol positif dan cuka apel ada kemiripan. Kata Kunci: Cuka Apel, Kolesterol Total, Hiperkolesterolemia.